Is it Possible Artificial Sex Regulation in Mammals? (Global Journal of Science Frontier Research, 2013)
In spite of, impressive breakthrough in modern genetics and molecular biology the problem of artificial sex regulation of mammals still remains unsolved. Moreover, the very problem of sex origin of eukaryotes in the process of evolution still has not settled. Existing theories and hypothesizes mainly concern the maintenance and biological reasonability of sexual mode of replication. Their theoretic foundation is based on Darwin's and Mendel's ideas that sex was originated due to natural selection and genes. On the basis of other model of genesis and sex evolution of eukaryote, it was suggested the idea of artificial sex regulation of mammals. Seemingly, the sex differentiation (SD) in animals and human is determined by the amount of constitutive heterochromatin region (cHR) in the Y chromosomes of the undifferentiated embryonic gonads (UEG) via cell thermoregulation. It is assumed the medulla and cortex tissue cells in the UEG differ in vulnerability to the increase of the intracellular temperature because of their anatomical position in genital ridges. If the amount of the cHR on Y chromosome is enough for efficient elimination of redundant metabolic heat from rapidly growing UEG cells the medulla tissue survives. Otherwise it doomed to degeneration and a cortex tissue will remain in the UEG. For artificial regulation of the SD it is proposed to remove a layer of cortex in the UEG.
Keywords: sex differentiation; sex regulation; cell thermoregulation; constitutive heterochromatin; Y chro-mosome; genital ridges; non coding DNAs